Histological studies on some native perennials - Tar, T.; Kohut, I.; Gracza, P. (International Journal of Horticultural Science, 2005)
Growing of native perennial species became more and more popular in the last ten years. In order to obtain more information on their histological structure, investigations were done on Aster linosyris, Inula ensifolia and Prunella grandiflora. The histological features are usually relating to the plants’ ecological demands which is an important aspect in their growing. Differences were found in the structure of the stem of Asteraceae and Lamiaceae members. While separated vessels were formed in the stem of Aster linosyris and Inula ensifolia, continuous vessel-system forms in the stem of Prunella. Alternating segments of collenchyma and chlorenchyma are found in the stem of Aster linosyris, while palisade parenchyma is situated both on the abaxial and adaxial surface of the leaves. Vessel-system of the root is tetrarch. Histological structure of the stem of Inula ensifolia differs from Aster linosyris in the broader cortical parenchyma which is composed of approx. 8-12 cell layers. It contains neither collenchyma nor chlorenchyma. In the stem of Prunella grandiflora a nearly continuous vessel-ring is formed from the four primary vessels. Long, multi-celled hairs were observed in the district of angles of the stem.